2020
DOI: 10.1002/jcp.29913
|View full text |Cite
|
Sign up to set email alerts
|

Osthole interacts with an ER‐mitochondria axis and facilitates tumor suppression in ovarian cancer

Abstract: Osthole is a natural coumarin found in a variety of plants and has been reported to have diverse biological functions, including antimicrobial, antiviral, immunomodulatory, and anticancer effects. Here, we investigated the natural derivative osthole as a promising anticancer compound against ovarian cancer and evaluated its ability to suppress and abrogate tumor progression. In addition, we found the endoplasmic reticulum-mitochondrial axis-mediated anticancer mechanisms of osthole against ES2 and OV90 ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…S1 ), consistent with its known anticancer effect. We then examined whether any of the following natural compounds, apigenin [ 18 ], carvacrol [ 19 ], chrysin [ 20 ], coumestrol [ 21 ], curcumin [ 22 ], delphinidin [ 23 ], formononetin [ 24 ], naringenin [ 25 ], osthole [ 26 ], quercetin [ 27 ], silibinin [ 28 ], and stigmasterol [ 29 ], at 20 μM potentiated the anticancer effect of 5-FU (20 μM) for 48 h ( Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…S1 ), consistent with its known anticancer effect. We then examined whether any of the following natural compounds, apigenin [ 18 ], carvacrol [ 19 ], chrysin [ 20 ], coumestrol [ 21 ], curcumin [ 22 ], delphinidin [ 23 ], formononetin [ 24 ], naringenin [ 25 ], osthole [ 26 ], quercetin [ 27 ], silibinin [ 28 ], and stigmasterol [ 29 ], at 20 μM potentiated the anticancer effect of 5-FU (20 μM) for 48 h ( Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research regarding the cytotoxic and antitumor activity of osthole has involved various kinds of tumor cells/models as showed in Table 2. These include breast cancer cells [26][27][28][29], ovarian carcinoma (OC) cells [30][31][32], endometrial carcinoma (EC) cells [33], head and neck squamous cell carcinoma (HNSCC) cells [34], hepatocellular carcinoma (HCC) cells [35][36][37], human gastric cancer cells [38,39], cervical cancer cells [40][41][42], rhabdomyosarcoma (RMS) cells [43], intrahepatic cholangiocarcinoma (ICC) cells [44], esophageal squamous cell carcinoma (ESCC) cells [45], renal cell carcinoma (RCC) cells [46,47], nasopharyngeal cancer (NPC) cells [48], bladder cancer cells [49], lung cancer cells [50][51][52], leukemia cells [53,54], osteosarcoma (OS) cells [55], human melanoma cells [56], and glioma cells [57].…”
Section: Cytotoxic and Antitumor Activitymentioning
confidence: 99%
“…For example, osthole inactivates PI3K/AKT signaling pathway and represses the malignant phenotypes of gastric cancer cells [ 18 ]. Its anticancer ability was also described in pancreatic cancer [ 15 ], gallbladder cancer [ 19 ], and ovarian cancer [ 20 ]. In cervical cancer, Su et al demonstrated that osthole showed increase in the inhibition of cisplatin on NRF2 expression, thereby eliminating drug resistance of tumor cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%